Effort-Reward Imbalance in Emergency Department Physicians: Prevalence and Associated Factors - Tian, Mengge; Zhou, Xuan; Yin, Xiaoxv; Jiang, Nan; Wu, Yafei; Zhang, Jiali; Lv, Chuanzhu; Gong, Yanhong (Frontiers in Public Health, 2022)
Objectives: To examine the prevalence of effort-reward imbalance and explore its associated factors among emergency department physicians in China. Methods: A cross-sectional survey was conducted in the Chinese emergency department in 2018. A total of 10,457 emergency department physicians completed a structured questionnaire containing demographic characteristics, work-related data, and effort-reward imbalance scale. All the data were analyzed using descriptive analysis and stepwise logistic regression. Results: The prevalence of effort-reward imbalance was 78.39% among emergency department physicians in China. The results showed that the male emergency department physicians with a bachelor’s degree, an intermediate title, long years of service, a high frequency of night shift, and who suffered workplace violence were at a higher risk of effort-reward imbalance. In contrast, physicians with higher monthly income and perceived adequate staff were associated with a lower risk of effort-reward imbalance. Conclusions: The situation of effort-reward imbalance was serious among emergency department physicians in China. Administrators should pay more attention to key groups and take measures from the perspectives of effort and reward to improve the effort-reward imbalance in emergency department physicians.